Variations in the cytotoxic glycoalkaloids solamargine and solasonine in different parts of the Solanum incanum plant during its growth and development in Oman. Issue 6 (1st October 2016) - Al Sinani, Sana S.; Eltayeb, Elsadig A.; Kamal, Y.T.; Khan, Masood S.; Ahmad, Sayeed
Abstract: In addition to several important traditional medicine applications of Solanum incanum, the plant is a rich source of important cytotoxic glycoalkaloids, such as solamargine and solasonine. Because S. incanum is a potential source of compounds for steroid synthesis, it is worthwhile to study the content of these important glycoalkaloids during plant developmental stages. Therefore, an attempt has been made to quantitatively estimate solasonine and solamargine content using an optimized isolation process and a newly developed and validated HPTLC method using different parts of S. incanum plants at different developmental stages and comparing changes in the whole-plant GAs profile during the growth and development of S. incanum plants in Oman. Solamargine and solasonine produced well-separated compact bands with R f values of 0.26 and 0.14, respectively, on silica gel HPTLC plates using chloroform:methanol:5% ammonia (7:3:0.5, v/v/v) after visualization using anisaldehyde sulphuric acid reagent. The chromatograms were scanned at 530 nm wavelength and the simultaneous method was linear ( r 2 ≥ 0.9962) in concentrations ranging from 50 to 2000 ng/spot for both of the drugs. The validated method was applied to analyse solamargine and solasonine in small, young, immature and mature leaves as well as stem and root parts up to the 40th week of plants' growth, and showed a rich concentration of glycoalkaloids with large variations at different stages of plant development. Hence, this study highlights the importance of developmental stages of particular organs and the overall age of the plant when harvesting for these GAs from S. incanum plants.